Are our ‘UHC systems’ learning systems? Piloting an assessment tool and process in six African countries? - Akhnif, Eucine; Kiendrebeogo, Joel .Arthur; Azouzzi, Idrissi; Makout, CODJO ABODOURIN ALBERT CHARLES PATRICK (My University, 2018)
Background: If there is one universal recommendation to countries wanting to make progress towards Universal Health Coverage (UHC), it is to develop the learning capacities that will enable them to ‘find their own way’ – this is especially true for countries struggling with fragmented health financing systems. This paper explores results from a multi-country study whose main aim was to assess the extent to which UHC systems and processes at country level operate as ‘learning systems’. Method: This study is part of a multi-year action-research project implemented by two communities of practice active in Africa. For this specific investigation, we adapted the concept of the learning organisation to so-called ‘UHC systems’. Our framework organises the assessment around 92 questions divided into blocks, sub-blocks and levels of learning, with a seven scale score in a standardised questionnaire developed during a protocol and methodology workshop attended by all the research teams. The study was implemented in six francophone African countries by national research teams involving researchers and cadres of the ministries involved in the UHC policy. Across the six countries, the questionnaire was administrated to 239 UHC actors. Data were analysed per country, per blocks and sub-blocks, by levels of learning and per question. Results: The study confirms the feasibility and relevance of adapting the learning organisation framework to UHC systems. All countries scored between 4 and 5 for all the sub-blocks of the learning system. The study and the validation workshops organised in the six countries indicate that the tool is particularly powerful to assess weaknesses within a specific country. However, some remarkable patterns also emerge from the cross-country analysis. Our respondents recognise the leadership developed at governmental level for UHC, but they also report some major weaknesses in the UHC system, especially the absence of a learning agenda and the limited use of data. Conclusion: Countries will not progress towards UHC without strong learning systems. Our tool has allowed us to document the situation in six countries, create some awareness at country level and initiate a participatory actionoriented process.
Keywords: Universal health coverage; Health system; Learning organisation; Participatory research; Capacity-building; Africa